Prophetic Education: Understanding the Relevance of Qur'anic Verses in the Context of Modern Education - Achmadin, Balya Ziaulhaq; Anggraini, Reni Dwi; Ulum, Moh. Samsul; Masuwd, Mowafg (Al-Riwayah : Jurnal Kependidikan, 2025)
This study aims to analyze the concept of prophetic education contained in the verses of the Qur'an and its relevance in prophetical education. Descriptive-analytical approaches are used by collecting primary data from the literary study of the Qur'an and secondary data of related books and scientific articles. Research results show that the verses of the Qur'an contain important concepts in prophetic education, such as emphasis on the importance of education, the development of good morals, justice, equality, and a compassionate approach to education. The prophet (peace and blessings of Allah be upon him) is a prophet of the Qur'an. This research contributes to an understanding of prophetic education based on the Qur'an and can be used as a reference for educators, educational policymakers, and researchers in designing educational programmes that are oriented towards the values and principles of prophecy education.